Pseudo-Lignin Content Decreased with Hemicellulose and Lignin Removal, Improving Cellulose Accessibility, and Enzymatic Digestibility - Schmatz, Alison Andrei [UNESP]; Salazar-Bryam, Ana Maria [UNESP]; Contiero, Jonas [UNESP]; Sant’Anna, Celso; Brienzo, Michel [UNESP] (Springer Nature, 2020)
The sugarcane bagasse is a heterogeneous material and needs a pretreatment to breakdown its complex structure to make cellulose accessible to enzyme action. This study aimed to evaluate pseudo-lignin formation, enzymatic hydrolysis of sugarcane fractions (leaf, external fraction, internode, and node), and bagasse after partial delignification and acid pretreatment. The leaf and external fraction presented the highest content of lignin, and external fraction was the most recalcitrant material resulting in lower glucose release. Pretreatment with diluted sulfuric acid (20% m/m or 2% m/v) generated 5 g/L of acetic acid and 2.07 g/L of 5-hydroxymethylfurfural (external fraction in natura and leaf extractive-free, respectively). Furfural ranged between 0.11 g/L (node delignified) and 0.06 g/L (leaf, external fraction, and node in natura). A decrease was observed in pseudo-lignin formed with extractive-free and delignified biomasses, with different structure compared with non-delignified samples. The biomass partial delignification and subsequent pretreatment with dilute acid generate a material with fragmented anatomical structure, with improved cellulose accessibility, favoring enzymatic hydrolysis achieving more than 90% of glucose yield (up to 12 g/L). This study has shown strategies to decrease material heterogeneity and avoid pseudo-lignin formation as it results in lower recalcitrance and better efficiency of the enzymatic hydrolysis.
Keywords: Cellulose; Diluted acid pretreatment; Extractives; Glucose; Sugarcane fraction